Characteristics and Antibacterial Activity of Chitosan and Green Tea Extracts in Mouthwash - Pidada, Hijria Mardhilla; Indrani, Decky Joesiana (FKG Universitas Syiah Kuala, 2025)
Dental caries and gingivitis can be mitigated through the use of mouthwashes. However, chemical-based mouthwashes are associated with several adverse effects. Safer alternatives to chemical mouthwashes incorporate natural ingredients. Chitosan and green tea have gained prominence in the synthesis (formulation) of mouthwashes, with a focus on characterizing their antibacterial properties. This overview will concentrate on the synthesis methodology, characteristics, and antibacterial efficacy of chitosan and green tea. Chitosan and green tea mouthwashes can be synthesized using the solubilization method. This method entails the creation of a thermodynamically stable, isotropic solution of a substance in water by the addition of a surfactant. Chitosan is distinguished by the presence of glucosamine and N-acetylglucosamine repeating units, both of which contain amino groups. These amino groups exhibit antibacterial properties by interacting with bacterial cell membranes and compromising their structural integrity. In green tea, compounds such as catechins within phenolic groups, including flavanols, flavandiols, and flavonoids, also function as agents by disrupting bacterial cell membranes and cytoplasmic membranes. Both amino groups and catechin compounds demonstrate the ability to inhibit pathogenic oral bacteria. In conclusion, the potentially anti-bacterial activity mouthwashes synthesized from chitosan and green tea, in the future chitosan and green tea extracts to be further used for the preparation of mouthwash.